2011
DOI: 10.1093/infdis/jir347
|View full text |Cite
|
Sign up to set email alerts
|

Kunjin Virus Replicon-Based Vaccines Expressing Ebola Virus Glycoprotein GP Protect the Guinea Pig Against Lethal Ebola Virus Infection

Abstract: Pre- or postexposure treatments against the filoviral hemorrhagic fevers are currently not available for human use. We evaluated, in a guinea pig model, the immunogenic potential of Kunjin virus (KUN)-derived replicons as a vaccine candidate against Ebola virus (EBOV). Virus like particles (VLPs) containing KUN replicons expressing EBOV wild-type glycoprotein GP, membrane anchor-truncated GP (GP/Ctr), and mutated GP (D637L) with enhanced shedding capacity were generated and assayed for their protective efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…Another VLP-producing approach is to use a replicon-recombinant kunjin virus, expressing VLPs with full length Ebolavirus GP or a mutated (D637L) GP. These replicon VLPs induced dose-dependent protection in guinea pigs against a lethal challenge of an adapted Ebolavirus strain [128].…”
Section: Vaccinesmentioning
confidence: 99%
“…Another VLP-producing approach is to use a replicon-recombinant kunjin virus, expressing VLPs with full length Ebolavirus GP or a mutated (D637L) GP. These replicon VLPs induced dose-dependent protection in guinea pigs against a lethal challenge of an adapted Ebolavirus strain [128].…”
Section: Vaccinesmentioning
confidence: 99%
“…42 Reynard et al 43 developed KUN VLPs expressing Ebola virus GP, which were capable of infecting and delivering replicon RNA into most mammalian cell types. Later the vaccines were evaluated in guinea pig model in 2009, vaccinating female, 3-week-old Dunkin-Hartley guinea pigs with 1 £ 10 6 or 5 £ 10 6 vp KUN VLPs expressing fulllength wild-type or D637L-mutated GPs or GP/Ctr intraperitoneally.…”
Section: Kun Vlpsmentioning
confidence: 99%
“…Later the vaccines were evaluated in guinea pig model in 2009, vaccinating female, 3-week-old Dunkin-Hartley guinea pigs with 1 £ 10 6 or 5 £ 10 6 vp KUN VLPs expressing fulllength wild-type or D637L-mutated GPs or GP/Ctr intraperitoneally. 43 Then, 20 d after the prime vaccination, a boosting immunization with the same dosage and type of KUN VLPs was administrated. Only 25%»75% of guinea pigs inoculated with KUN VLPs expressing full-length wild-type or D637L-mutated GPs survived after challenging with a lethal dose of 200 LD 50s of recombinant guinea pig-adapted EBOV.…”
Section: Kun Vlpsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the efficacy of vaccines observed in rodents does not always extend to primates [26], GP-VRP was evaluated in cynomolgus macaques in 2013 and found that a single dose could provide complete protection against intramuscular challenge [58]. membrane anchor-truncated GP and D637L-mutated GP [59]. The surviving animals showed complete clearance of the virus, but the anti-GP-specific antibody response was found to be variable between them.…”
Section: Venezuelan Equine Encephalitis Virus (Veev)-like Replicon Pamentioning
confidence: 99%